Bearings : basic concepts and design applications - Adams, Maurice L., Jr (CRC Press, 2017)
Bearings: from Technoloogical Foundations to Practical Design Applications provides a modern study of bearing types, design factors, and industrial examples. The major classes of bearings are described, and design concepts are covered for rolling elements, surfaces, pivots, flexures, and compliance surfaces. Fluid film lubrication is presented, and the basics of tribology for bearings is explained. The book also looks at specific applications of bearing technology, including bearings in vehicles, rotating machinery, machine tools, and home appliances. Case studies are also included.
Keywords: Bearings (Machinery); elektronické knihy; electronic books